(untitled) (Journal of Hama University, 2025)
The reasons for the vevelation of the qur,anic verses are an integrated science that has its own theary and applications It is also closely Sciences, which are integrated to serve the Holy Qur,an . Knowing the reasons for the decline is of great indispensable importance for understanding the correct and Precise meaning intended from the Qur,anic verses that were revealed for aveason . One of the most important abgectives of this research is to identify the usefulness of the reasons for the revelation and its impact in deriving jurisprudential vulings from the verses of rulings that were revealed due to a specific incident or inresponse to aguestion asked to the prophet,may God bless him and grant himpeace . This research was ascientific contribution to the knowledge building of this art of Islamic law sciences . In order for the research to achieve its purpose, it took the inductive and analytical approach in its treatment within two reguirements : The first is theoretical for the general definition that teaches the reasons for the revelation, and the second is practical for explaining the effect of the reason for the revelation in deducing the jurisprudential rulings is Surat Al-Ma,idah .